Performance appraisals in public and private sectors: Attitudes and perceptions of employees - Martin Golob; Marino Golob; Veronika Vnučec (Elektronički Zbornik Radova Veleučilišta u Šibeniku, 2024)
The aim and purpose of the study is to find out the attitudes and perceptions of employees related to the performance appraisals in their organizations, considering their affiliation with the public or private sector and the size of the organization. Within the study, research objectives are set regarding understanding recent attitudes related to organization and work classification, the frequency of performance evaluation, internal communication related to performance evaluation, employee involvement in the management of work performance, as well as characteristics of the system itself and general attitudes towards work performance evaluation. A survey questionnaire was used in the study, and the sampling method employed was the snowball sampling method. Descriptive statistics, t-tests, and ANOVA analysis were used for analysis. Potentially interesting conclusions were observed in the study, along with correlations between attitudes related to work performance evaluation, some of which are statistically significant, and the results can be applied to a broader population. One of the key conclusions is that an effective and clearly defined system of work performance evaluation and management is interconnected with operational procedures regarding the regular implementation of evaluation, communication regarding evaluation, the purpose of evaluation, and employee involvement, and that in Croatian companies, evaluation is not merely formal. Differences in employee attitudes between the public and private sectors, as well as across different organization sizes, are neither statistically significant nor different to a large extent, but they still provide insights into employee perceptions that can be useful in managing the work performance evaluation system and its implementation in decision-making processes within business entities.